Balanced Budget Rules and Fiscal Outcomes: Evidence from Historical Constitutions - Zareh Asatryan; César Castellón; Thomas Stratmann (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper studies the long-run fiscal consequences of balanced budget rules (BBR) that are enshrined in a country's constitution. Using historical data dating back to the 19th century and applying a difference-in-difference approach we find that the introduction of a constitutional-BBR reduces government debt-to-GDP and expenditure-to-GDP ratios, on average, by around 11 and 3 percentage points, respectively. We do not find evidence that BBRs also affect tax revenues. Our analysis demonstrates that such rules reduce the probability of experiencing a debt crisis, and that the effective enforcement of BBRs can be conditional on the quality of democratic institutions. In addition, we implement an instrumental variable approach by instrumenting the probability of having budget rules on de jure constraints on changing the constitution. This and other tests suggest that the relations we find are largely causal going from BBRs to fiscal outcomes.
Keywords: H50; H60; K10; N40; 330; economic effects of constitutions; fiscal rules; historical public finances; sovereign debt crises